Efficacious treatment of psoriasis with low‐dose and intermittent cyclosporin microemulsion therapy. Issue 5 (15th March 2014) - Ito, Taisuke; Furukawa, Fukumi; Iwatsuki, Keiji; Matsue, Hiroyuki; Shimada, Shinji; Takigawa, Masahiro; Tokura, Yoshiki
Abstract Cyclosporin is used for moderate to severe psoriasis and improves not only the skin lesions but also quality of life of the patients. To improve its safe use, we evaluated a low‐dose, intermittent regimen of cyclosporin in the treatment of psoriasis vulgaris. Seventy‐three patients received approximately 2.5 mg/kg per day of cyclosporin microemulsion twice daily before breakfast and dinner for 2–12 weeks until 75% reduction was achieved in Psoriasis Area and Severity Index (PASI) score. When the skin lesions relapsed after cessation of cyclosporin and showed less than 50% reduction from baseline in PASI score, cyclosporin was restarted. This cessation and restart cycle was repeated if necessary. Treatment outcomes were assessed at 12, 48 and 96 weeks after initiation of the therapy. The initial dose of cyclosporin was 2.32 ± 0.27 (standard deviation [SD]) mg/kg per day. At baseline, the mean PASI score was 11.3 ± 5.3 (SD). An average of 49.8 ± 23.8 (SD) days of the therapy achieved PASI 75% reduction. In 20 of 73 patients, the second course of cyclosporin was required. The mean interval between the first and second course was 94 days. An average of 60.8 ± 26.9 days was required to achieve PASI 75% reduction in the second course, which was not significantly longer than that in the first course. Only six patients required cyclosporin for 96 weeks. The adverse effects included one case of hypertension. Our study suggests that low‐dose, intermittent cyclosporin microemulsion is efficacious for the treatment of moderate to severe psoriasis.